La touristification de la vie nocturne : une nouvelle frontière pour la recherche sur la nuit urbaine - Emanuele Giordano; Jordi Nofre Mateu; Dominique Crozat (Cybergeo, 2018)
The last two decades have witnessed the emergence of a growing interest in the evolution of the urban night. However, the touristification of the urban night has received only limited attention in contemporary social sciences. Until now, academic research has explored night tourism mainly in relation to specific contexts or events: tourist resorts or springbreaks.The focus was placed on the health and safety risks associated with excessive drinking, recreational drug use and casual sex. More recently, researchers have begun to theorize these forms of holiday as a form of temporary departures from the participants' daily lives. While this vision of night tourism as a temporary departure is still dominant, recent studies have revealed a more complex reality. For this reason, this paper proposes the development of a new research agenda aimed at questioning the progressive diversification of tourist practices during the night in the city and the urban issues that these dynamics produce.